2016
DOI: 10.1016/j.resuscitation.2016.05.019
|View full text |Cite
|
Sign up to set email alerts
|

Using the relationship between brain tissue regional saturation of oxygen and mean arterial pressure to determine the optimal mean arterial pressure in patients following cardiac arrest: A pilot proof-of-concept study

Abstract: We demonstrated the feasibility to determine a MAPOPT using cerebral oximetry in patients after cardiac arrest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
55
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(58 citation statements)
references
References 34 publications
3
55
0
Order By: Relevance
“…indicate that wavelet NIRS indices may be accurate methods to monitor autoregulation with lower signal variation than commonly used correlation indices [2][3][4] in pediatric cardiac arrest.…”
Section: Discussionmentioning
confidence: 97%
“…indicate that wavelet NIRS indices may be accurate methods to monitor autoregulation with lower signal variation than commonly used correlation indices [2][3][4] in pediatric cardiac arrest.…”
Section: Discussionmentioning
confidence: 97%
“…Although higher COx was associated with nonsurvivors, there was no association between rSO 2 and mortality. Recently, our research team demonstrated feasibility of monitoring COx in real time and identification of optimal MAP prospectively in 20 patients after CA [55]. Subjects spent approximately 50% of time outside a ±5 mmHg range from the optimal MAP, and, importantly, the optimal MAP was consistently identified in 19 of 20 subjects.…”
Section: Secondary Injurymentioning
confidence: 99%
“…Increased cerebral metabolism, hyperemic blood flow, and increased ICP are additional downstream consequences of uncontrolled hyperthermia in HIBI [3]. Recently, we showed that hyperthermia is associated with dysfunctional autoregulation in patients with HIBI [55]. …”
Section: Secondary Injurymentioning
confidence: 99%
“…There is no standard value of MAP that would be appropriate for all hemodynamic targets (Ameloot et al, 2015). Due to an impaired CVAR, we could control MAP by measuring rSO 2 to avoid brain ischemia for PCAS management (Sekhon et al, 2016).…”
Section: Discussionmentioning
confidence: 99%